2015
DOI: 10.1038/onc.2015.415
|View full text |Cite
|
Sign up to set email alerts
|

NAMPT suppresses glucose deprivation-induced oxidative stress by increasing NADPH levels in breast cancer

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) is a rate-limiting enzyme involved in NAD+ biosynthesis. Although NAMPT has emerged as a critical regulator of metabolic stress, the underlying mechanisms by which it regulates metabolic stress in cancer cells have not been completely elucidated. In this study, we determined that breast cancer cells expressing a high level of NAMPT were resistant to cell death induced by glucose depletion. Furthermore, NAMPT inhibition suppressed tumor growth in vivo in a xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…In this study we suggested that SIRT6 can prevent oxidative stress damage in cells through up-regulation of NAMPT activity and increase in NADPH, as a consequence of G6PD activation. This result is in line with a study reporting that, in breast cancer cells, NAMPT activity counteracts glucose deprivation-induced oxidative stress by inducing an increase in NADPH (10). Thus, our observations indicate that SIRT6 is a key upstream player regulating NAMPT activity in these events.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we suggested that SIRT6 can prevent oxidative stress damage in cells through up-regulation of NAMPT activity and increase in NADPH, as a consequence of G6PD activation. This result is in line with a study reporting that, in breast cancer cells, NAMPT activity counteracts glucose deprivation-induced oxidative stress by inducing an increase in NADPH (10). Thus, our observations indicate that SIRT6 is a key upstream player regulating NAMPT activity in these events.…”
Section: Discussionsupporting
confidence: 93%
“…NAMPT inhibition with FK866 also affects the NADP(H) pool, although to a different extent, depending on the cell type (8,9). Notably, in breast cancer cells, the NAMPT-mediated increase in NAD + levels has been shown to be paralleled by an increase in NADPH through the pentose phosphate pathway, resulting in tumor cell protection from glucose deprivation-induced oxidative stress (10).…”
mentioning
confidence: 99%
“…10 In a previous study, we reported that NAMPT could increase the antioxidant capacity of cancer cells and induce cancer cell survival under excessive oxidative stress upon glucose deprivation. 15 Consistently, NAMPT expression was not induced by H 2 O 2 treatment in normal cells, but it was dramatically increased in CRC cells ( Figure 4C), indicating that NAMPT expression in tumor tissues could be increased due to inflammation-induced ROS production. In tissues of CRC patients, both mRNA and protein levels of NAMPT were also upregulated ( Figure 6F-I).…”
Section: Discussionsupporting
confidence: 56%
“…Cancer cells that survive despite oxidative stress are likely to have acquired adaptive mechanisms to counteract the potential toxic effects of elevated ROS . In a previous study, we reported that NAMPT could increase the antioxidant capacity of cancer cells and induce cancer cell survival under excessive oxidative stress upon glucose deprivation . Consistently, NAMPT expression was not induced by H 2 O 2 treatment in normal cells, but it was dramatically increased in CRC cells (Figure C), indicating that NAMPT expression in tumor tissues could be increased due to inflammation‐induced ROS production.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation